Novel Roles of Follistatin/Myostatin in Transforming Growth Factor-β Signaling and Adipose Browning: Potential for Therapeutic Intervention in Obesity Related Metabolic Disorders - Pervin, Shehla; Reddy, Srinivasa T.; Singh, Rajan (Frontiers in Endocrinology, 2021)
Obesity is a global health problem and a major risk factor for several metabolic conditions including dyslipidemia, diabetes, insulin resistance and cardiovascular diseases amongst many others. Obesity develops from a chronic imbalance between energy intake and energy expenditure. Stimulation of cellular energy burning process has the potential to dissipate excess surplus calories in the form of heat via the activation of uncoupling protein-1 (UCP1) in white and brown adipose tissues. Recent studies have shown that activation of transforming growth factor-β (TGF-β) signaling pathway significantly contribute to the development of obesity, and blockade of this pathway is reported to protect from obesity by promoting white adipose browning and increasing mitochondrial biogenesis. Identification of novel compounds that can activate beige/brown adipose characteristics to burn surplus calories and reduce excess storage of fat could provide avenues for therapeutic drug design to fight against obesity. Follistatin (Fst) and myostatin (Mst) are two key members of TGF-β superfamily which are recently identified as key regulators of adipose browning and influencers of classical brown adipose tissue mass and its activity through distinctly different pathways. Here, we review the data supporting the critical roles of TGF-β/Fst/Mst signaling in regulating beige and brown adipose characteristics as potential therapeutic avenues for the treatment of obesity and related metabolic disorders.